딸기분말을 첨가한 국수의 품질 특성 - 박복희; 고경미; 차민혜; 김옥주; 전은례; Bock-Hee Park; Kyeong-Mi Koh; Min-hye Cha; Ok-Joo Kim; Eun-Raye Jeon (Journal of the Korean Society of Food Culture, 2016)
This study evaluated the quality characteristics of dried noodles prepared with strawberry powder in order to determine the most preferred noodle recipe for children’s school meals. The proximate composition of strawberry powder used was as follows: moisture, 3.39%; crude protein, 1.53%; crude lipid, 0.97%; crude ash, 0.82%; and carbohydrates, 93.29%. When viscosity of the composite strawberry powder-wheat flours was measured by amylograph. Gelatinization point, maximum viscosity, viscosity at 95oC and viscosity at 95oC after 15 min decreased as the level of strawberry powder increased. As the level of strawberry powder increased, both L and b color values decreased, whereas a value increased. Weight, water absorption and volume of cooked noodles decreased, whereas turbidity of soup increased. For textural properties, addition of strawberry powder to cooked noodles reduced hardness, chewiness and brittleness. Overall preference according to the results of the sensory evaluation, noodles added with 6% strawberry powder were the most preferred. According to the results, the addition of strawberry powder can positively affect the overall sensory evaluation of dried noodles, and 6% is the optimal level for addition.